Pengaruh Faktor Dukungan Keluarga Dan Masyarakat Terhadap Depresi Pasca Melahirkan Pada Perilaku Ekstrem Seorang Ibu - Dewi Nurhaji Meivita; Lika Hestiyaningsih (Universitas Darul Ulum, 2025)
The incidence of baby blues syndrome in Indonesia shows varying numbers in each region, which is around 50% to 70% of all mothers who give birth. The last five years have been recorded in electronic media from 2019 to 2024, during which time there have been several cases of the loss of life of babies and toddlers by their biological mothers. After being investigated, this was caused by several factors, including support from those closest to them, namely the family, especially the husband. This study examines existing cases with respondent data, specifically a mother who has given birth. Testing on respondents using the EPDS method which will be validated by how big the role of the husband and family is in parenting and care. It was found that 4 out of 10 mothers who gave birth experienced postpartum depression, and all of them had thought about hurting themselves or others. The influence of the husband in the process of recovering from depression in mothers is very influential, because all respondents never reached the point of carrying out extreme behavior to hurt themselves or their children. This is influenced by the husband's role in child care and mother care.